(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2025)
This research aims to design a web based sales information system to increase the effectiveness of recording transactions at Subur Building Shop Kaliwungu which was previously still done manually. The main problems faced include inefficient recording, difficulty searching data, and lack of accuracy in financial reports. The research method used is qualitative with a Research and Development (R&D) approach using a Prototype model. The system was developed by applying the Accrual Basis accounting method so that financial reports can be prepared more accurately and in real time. The results showed that the system is able to record sales and purchase transactions, manage goods and customer data, and present sales report and financial statements digitally. Additional features such as transaction history, stock information, and profit and loss calculation also help store owners in decision making. The implementation of the system has a positive impact, including increased efficiency, data accuracy, and ease of monitoring sales activities.